Studi Deskriptif tentang Sarana dan Prasarana Bimbingan dan Konseling di Sekolah Menengah Pertama - Dwi Putranti (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2015)
This study aims to determine the availability of facilities and infrastructure for guidance and counseling. This research is descriptive research with survey method, which is housed in the city of Yogyakarta with research subjects across the school SMP Muhammadiyah in Yogyakarta at 10 schools. Data collection tool that is used in the form of a semi-open questionnaire which contains a checklist availability of facilities and infrastructure for guidance and counseling in schools. Data analysis techniques used in the form of descriptive statistics. The results showed 1) the availability of counseling rooms were adequate according to the standard which is sized 8x 9 m, new in 5 (50%) of schools that meet the standards of the 10 schools that became the subject of research; 2) the availability of special counseling room owned by the 8 schools (80%) of the 10 schools; 3) The factors inhibiting the availability of counseling that factor in the cost and land constraints. The results provide information for the development of facilities and infrastructure, principals, homeroom and subject teachers about the limited facilities BK teachers in providing services BK to students, so as to help teachers BK in providing the necessary facilities to make students feel comfortable in obtain guidance and counseling services in schools.